Principles of Database Systems / Second Edition - Ullman, Jeffrey D. (Computer Science Press, 1982)
Descriptions of actual database systems and query languages such as ISBL, QUEL, Query-by-Example, and SEQUEL are also included, making this book ideal for both practicing computer scientists and for database courses. Introduction to Database System Concepts, Physical Data Organization, The Network Model and the DBTG Proposal, The Hierarchical Model, The Relational Model, Relational Query Languages, Design Theory for Relational Databases, Query Optimization, The Universal Relation as a User Interface, Protecting the Database Against Misuse, Concurrent Operations on the Database, Distributed Database Systems, Bibliography, Index.